The treatment - Young, Suzanne (New York : Simon Pulse, 2014)
Working with rebels to bring down The Program, a suicide prevention treatment in which painful memories are erased, Sloane and James consider taking The Treatment to unlock their memories.
Sequel to: The program --Verso.
HL 700
Accelerated Reader AR
Keywords: Suicide -- Juvenile fiction; Government, Resistance to -- Juvenile fiction; Memory -- Juvenile fiction; Young adult fiction; Young adult fiction; Love stories; Science fiction